PENURUNAN BIAYA PRODUKSI PADA USAHATANI PADI SAWAH MELALUI PENDEKATAN PENGELOLAAN TANAMAN TERPADU DI KABUPATEN GROBOGAN - Sulamo Sulamo; Seno Basuki (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2004)
Rice as a staple food has a significant role on national economic. Until now rice farming is still being a backbone of rural economic system. To support its role, the study of Integrated Crop Management (ICM) was conducted in Grobogan Regency on cropping season I (2000/ 2001) and cropping season II (2001) respectively, to increase rice farming efficiency. The study was carried out on 5 hectares of land owned by 14 farmers which was then compared to IO non cooperator farmers. Technologies of ICM consisted of seeds treatment, young age planting material with single seedling per hill, fine compost application, N fertilizing based on leaf color chart, P and K fertilizing based on soil test, and intermitten irrigation. Data which was collected covered input use, cost of production, and grain yield. Data related to characteristic of rice farming were analyzed descriptively. Meanwhile, farming system per• formance was analyzed using Gross margin analysis. Results showed that during cropping season I (2001/01), cost production of ICM to produce of kilogram milled dry grain (mdg) (516 rupiahs) was lower compared to that on famer practices (646 rupiahs or reduced by 20,20 %. Similarly, ICM technolgy gave a lower Break-even Point (BEP) (3,824 kilogram mdg per hectare than that on farmers technology (4,298 kilogram mdg per hectare) with BC ratio at 2.02. In addition the ICM was able to increase benefit at 131 rupiahs per kilogram mdg or increased by 24.81 %. Similar case was observed in cropping season II (200 I) in which production cost to produce a kilogram mdg of ICM (628 rupiahs) was lower than farmer practices (741 rupiahs) or reduced by 15.25 %. Break-even Point of ICM (3,865 r kilogram mdg per hectare was also lower compared to farmers technology (4,796 kilogram mdg per hectare with BC ratio at 1.62. Whereas benefit obtained by ICM (389 rupiahs per kilogram mdg) was higher than that in farmer practices (182 rupiahs per kilogram mdg) or increased by 193.21 %.